The Risk Auditing for Accounting Standard Reform Through a Corporate Governance Perspective: A Case Study in Luckin Coffee - Cai, Quili; Rattanapun, Supot (Research in Social Sciences and Technology- OpenED Network, 2025)
This study investigates how risk auditing, accounting standards, and corporate governance influence accounting reforms in China's Luckin Coffee. Data were collected through in-depth, semi-structured interviews with 30 audit professionals from nine accounting networks. The gray correlation coefficient technique was used to assess the risks associated with Luckin Coffee, focusing on material misstatements at the financial reporting level. The analysis involved risk evaluation, judgment matrix consistency checks, and gray relational, descriptive, correlation, and content analyses. The findings reveal that: 1) The risk of material misstatement at the financial statement level was R1=0.473, and the risk at the hierarchical level was R2=0.527. 2) The highest audit risk factors, ranked by gray correlation degree, include: 1) Information system risk (0.754), 2) Management fraud risk (0.744), 3) Industry risk (0.733), 4) Revenue recognition (0.729), 5) Sales expenses (0.719), 6) Policy risks (0.719), 7) Supply chain management (0.585), 8) Business model risk (0.581), 9) Regulatory risk (0.546), and 10) Consumer acceptance (0.494). Corporate governance issues identified include: 1) Audit Committee neglect, and 2) Failure of the Nominating and Governance Committee. The study highlights key challenges in accounting standards reform: 1) Lack of effective monitoring, 2) Insufficient external oversight, and 3) Inadequate regulation of innovative retail models. The audit process for new retail business models poses unique regulatory challenges due to differences in distribution channels and customer service. This research contributes to achieving long-term goals of justice, peace, and economic progress.